2022
DOI: 10.1111/1541-4337.13017
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent progress in improving the bioavailability of nutraceutical‐loaded emulsions after oral intake

Abstract: Increasing awareness of the health benefits of specific constituents in fruits, vegetables, cereals, and other whole foods has sparked a broader interest in the potential health benefits of nutraceuticals. Many nutraceuticals are hydrophobic substances, which means they must be encapsulated in colloidal delivery systems. Oil‐in‐water emulsions are one of the most widely used delivery systems for improving the bioavailability and bioactivity of these nutraceuticals. The composition and structure of emulsions ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 308 publications
0
3
0
Order By: Relevance
“…In recent years, food-grade nanoparticle stabilized Pickering emulsion has attracted much attention and has been widely used in the delivery of bioactive substances ( Chen et al, 2020 ). Pickering emulsion is a kind of emulsion that is not stabilized by conventional emulsifier molecules but is formed by solid colloidal particles wetted by water and oil as stabilizers.…”
Section: Oil Oxidation Mechanism and Inhibition Strategymentioning
confidence: 99%
“…In recent years, food-grade nanoparticle stabilized Pickering emulsion has attracted much attention and has been widely used in the delivery of bioactive substances ( Chen et al, 2020 ). Pickering emulsion is a kind of emulsion that is not stabilized by conventional emulsifier molecules but is formed by solid colloidal particles wetted by water and oil as stabilizers.…”
Section: Oil Oxidation Mechanism and Inhibition Strategymentioning
confidence: 99%
“…Besides, the bioaccessibility of nutraceuticals and/or phytochemicals with hydrophobic characteristics can be improved by using different colloidal delivery systems, frequently through encapsulation methods (41,47) or emulsions (56). In certain cases, encapsulation techniques can be also applied to hydrophilic nutraceuticals (41).…”
Section: Nutraceuticals and Functional Foodsmentioning
confidence: 99%
“…The absorption process involves passive diffusion, and factors such as the presence of food and the formulation of API can influence its absorption rate. [16] Studies have shown that the absorption of API can vary among individuals, indicating potential interindividual differences in its BA.…”
Section: Pk and Bamentioning
confidence: 99%